Dry matter yield and essential oil of Baccharis trimera with mineral and organic fertilization - Amaral, Antonio Sergio do; Radünz, Lauri Lourenço; Mossi, Altemir José; Santi, Anderson; Rosa, Nádia Magali Farina Fiabane da; Feiten, Francisco (Revista de Ciências Agroveterinárias, 2010)
One of the main problems related to soil fertility for medicinal and aromatical plants is that official recommendations of liming and fertilization are only available for few species. This is a direct consequence of the scarce research performed in this area. Therefore, little is known regarding to the ideal soil type, the response to fertilization and liming and the effect of nutrients in the biologically active composite concentration of these species. This work was carried out aiming to evaluate the effect of different rates of NPK (10-30-15) and poultry manure on green and dry matter production, nutrient concentration (Ca, Mg, N, P, K, Cu, Zn and B) and shoot essential oil content of Baccharis trimera. The field work was carried out in a Rhodic Hapludox. The following treatments were tested: T1 (control - no fertilization); T2 (100 kg ha-1 of mixture 10-30-15); T3 (150 kg ha-1 of mixture 10-30-15); T4 (200 kg ha-1 of mixture 10-30-15); T5 (250 kg ha-1 of mixture 10-30-15); T6 (5 t ha-1 of poultry manure); T7 (10 t ha-1 of poultry manure) and T8 (15 t ha-1 of poultry manure). A randomized complete block design was used, with three repetitions. The average dry matter and essential oil yields were 10.3 t ha-1 and 134.5 L ha-1 respectively. Such productivities are considered high. Nonetheless, there were no statistically differences among treatments. This indicates that in limed soils, previously grown with other crops and presenting average organic matter content, Baccharis trimera can be produced without fertilization, using the available residual nutrients in the soil, at least for the first cut. The shoot accumulation of macro and micronutrients did not depend on the source and rate of fertilization. The oil yield was independent of the shoot nutrient content. Our results demonstrate that Baccharis trimera did not respond to mineral and organic fertilization.